Quantitative analysis of the prone stretching and adjusting neck manipulation based on motion capture technology and three-dimensional force measuring tables - Hong, Rui; Lin, Xiang-Ming; Yang, Chao; Zhang, Shi-Nian; Ye, Hua; Li, Ying (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study aimed to quantify the kinematic parameters of prone stretching and adjusting neck manipulation using motion capture technology and three-dimensional force measuring tables, thereby providing concrete evidence for standardising and scientifically grounding manual therapy training.MethodsTen patients with radiculopathy were recruited, and an experienced physician performed the prone stretching and adjusting neck manipulation. The kinematic data and ground reaction forces of the operator and the patients were synchronized using a Vicon 3D infrared motion capture system and a Kistler three-dimensional force measuring table.ResultsThe results of this study showed that when performing the “prone stretching and adjusting neck manipulation” manoeuvre, the maximum force loaded vertically by the active hand in the left and right rotational pulling (wrenching phase) was 551.5 N, and the minimum was 418.3 N, with a mean value of (476.75 ± 33.11) N. The maximum force loaded vertically in the left and right rotational pulling was 400.43 N, and the minimum was 182.4 N. The mean value was (274.79 ± 52.08) N. The manipulation trigger time was (0.35 ± 0.03) s, the maximum rotation angle was (73.7 ± 1.34)°, and the subject’s neck extension was (4.39 ± 1.02) mm.ConclusionThe “prone stretching and adjusting neck manipulation” is time-sensitive, short. The manoeuvre was divided into three phases: the stretching phase, the triggering phase, and the return phase. It involves both the active hand and the auxiliary hand, and the maximum force loaded in the vertical direction of the active hand is consistent in different operating directions.